A longitudinal qualitative study on lived experience of oral cancer patients during covid-19 pandemic in khyber pakhtunkhwa Pakistan - Khattak, Maria Ishaq (2023)
Oral cancer health experiences are profound and complex for patients even at the best of times. There is, however, little knowledge of how oral cancer patient’s health experiences may alter and develop in response to the COVID-19 pandemic's changing environment. This study explored the physical, social and psychological experiences of oral cancer patients at diagnosis, six months after diagnosis, and one year after diagnosis, with a particular focus on how experiences change through the different periods of time during the COVID-19 pandemic. Patients diagnosed with oral cancer at Khyber College of Dentistry, Peshawar, Pakistan were included in the study. The participants were selected using a maximum variation purposive sampling method to participate in this study. A longitudinal qualitative design was employed using the principles of phenomenological inquiry. Three semi-structured interviews were conducted as follows: at diagnosis (T1), six months after diagnosis (T2), and twelve months after diagnosis (T3). The sample at T1 and T2 comprised 17 participants. The sample at T3 comprised of a total 12 participants. The interviews were conducted in Pashto, the local language of Khyber Pakhtunkhwa. The audio-recorded interviews were transcribed ad verbatim in English and thematically analyzed. Data was organized using ATLAS.ti software version 8. Eight major broad-level themes were derived at T1: (1) pain and generalized physical weakness, (2) shock at diagnosis, (3) psychological distress of the COVID-19 pandemic, (4) faith and religion, (5) double hit loss of employment, (6) social isolation, (7) social support from caregivers, and (8) lack of support from health care professionals. At T2, five major broad-level themes were derived: (1) physical impairment and limitations, (2) psychological vulnerability, (3) reliance on God for protection, (4) availability of social support systems, and (5) financial decline. Finally, four major broad level themes were derived at T3: (1) the new normal, (2) the sum of fears, (3) belief in traditional healing practices, and (4) striving towards normalcy in social life. In conclusion, this longitudinal qualitative study provides insight into the complexities of living with oral cancer during the pandemic. The narratives in the study highlight conventional physical experiences while heightened psycho-social concerns at diagnosis. Patients social support slightly improved six months after diagnosis, but increased financial burdens, psychological distress, and physical symptoms continued. Finally, after twelve months, patients attempted to recover physically and gain social normalcy, but unwavering psychological concerns about the recurrence of oral cancer and the COVID- 19 pandemic lingered. The duality of the common oral cancer experiences and additional pandemic-inflicted experiences were evident in all three phases which affected the physical, psychological, and social well-being of oral cancer patients in Pakistan